Teachers' Perspectives on the Use of Telegram for Online Distance Learning During the Pandemic of COVID-19 - Zuraina, Ali; Sharifatun, Naim; Nabila, Abdul Malek; Hamizah, Zahari; Noraisah Nurul Fatwa, Mohd Razali (Association Res Militaris, 2022)
The pandemic of Covid-19 is a blessing in disguise. Academics seem to be using various ways to impart knowledge to their students as far as Online Distance Learning (ODL) isconcerned. One of the applications that they have chosen is Telegram. This study investigates the perceptions of academics teaching English using Telegram as a tool during ODL. The objectives of the study are to identify the academics' beliefs on the benefits of using Telegram, the perceived drawbacks of using Telegram in their teaching and learning, the reflections on the use of Telegram in classrooms, and the intentions of using Telegram during the post-pandemic. The study employed 66 instructors at tertiary level education and teachers teaching primary and secondary schools across Malaysia. The research employed a questionnaire to collect the data for the current study with closed and open-ended items. The results obtained from the study showed that Telegram could support teaching and learning during the pandemic, enhance communication between student-teachers by providing prompt responses, and be used to share information between students and teachers. The research implied that the use of Telegram is relevant, especially during this pandemic. Since teaching and learning is a mutual effort between teachers and students, it is encouraged that the former can assist the latter in making the classroom a fruitful session.